Inovasi Teknik Penebangan terhadap Perubahan Pengetahuan dan Sikap dalam Praktik Pengelolaan Hutan Rakyat di Desa Karyasari, Kecamatan Leuwiliang - Hardjanto, Hardjanto; Ilham, Qori Pebrial; Rahaju, Sri; Budiaman, Ahmad; Setiajiati, Fitta; Priyanto, Priyanto (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Private forests cultivated using agroforestry systems have the potential to produce timber, non-timber forest products, and a variety of agricultural crops. However, such forests are still being managed in a traditional manner, both in terms of cultivation techniques and management. The Service activities of the Dosen Pulang Kampung Program specifically aimed to introduce an innovative tree felling technique called the sandat technique, which minimizes the risk of damage to understory vegetation. The method used in this program is service learning, which integrates academic learning with community service through training sessions (both theoretical and practical). The results show that community forest farmers and loggers have understood this technique, recognizing it as a newly introduced method that they find highly beneficial and are eager to adopt in their forest-management practices. Consequently, they expressed their intention to adopt it for managing community forests. This innovation has started to demonstrate increased knowledge, a shift in attitudes (towards adoption), and satisfaction with the program itself. The Sandat Technique is thus critical to becoming a policy in community forest management and should be disseminated by the forestry office/branch to community forest farmers for adoption in the future.